IN MEMORY OF PIETRO PASSERINI - Abbate, Ernesto (Ofioliti, 2009)
Pietro Passerini was an important figure in Italian geology research of the second half of the 1900‘s, and left a vivid imprint also for his commitment in University politics. He was tenured professor of Geology at the University of Florence since 1972, then retired a few years ago. Pietro Passerini was for many of us an important guide both from a scientific and personal point of view. To remember him is like to trace the development of various aspects of geological research in Florence. In the 1960s, in Italy geology staff and students were mostly focussed on field work and mapping, to obtain a thorough detailed geologic map coverage of Italy. Pietro Passerini, a cunning observer and indefatigable hiker, climber (some of the climbing paths of the Apuan Alps were named after him) and mountain lover, was utterly fascinated by the challenges of field work.